Electromechanical flight stabilization system for CubeSat nanosatellites - Fausto R. Freire; Karla E. Mora (Dyna)
The objective of the research was to design and simulate a stabilization system for attitude control of CubeSat nanosatellites in LEO orbit. The electronic system was inside the mechanical system, designed in Proteus. The mechanical system was designed in SolidWorks, then a CubeSat 3U CAD was downloaded for simulation and finally, all CAD designs were assembled. These data were used for the analysis of the spatial environmental perturbations of aerodynamic drag, gradient, gravity and magnetic field.  Attitude representation was done by analyzing the Euler, Poisson and Quaternions equations. Then, a fuzzy logic control was created with two cases for automatic control. The analysis and virtual reality simulation revealed the correct attitude control on the CubeSat 3U nanosatellite, considering the perturbations of the space environment and a new 25° orientation of each axis.